Assessment of the Extrusion Process and Printability of Suspension-Type Drug-Loaded AffinisolTM Filaments for 3D Printing - Gloria Mora-Castaño; Mónica Millán-Jiménez; Vicente Linares; Isidoro Caraballo (MDPI AG, 2022)
Three-dimensional (3D) printing technology enables the design of new drug delivery systems for personalised medicine. Polymers that can be molten are needed to obtain extruded filaments for Fused Deposition Modelling (FDM), one of the most frequently employed techniques for 3D printing. The aim of this work was to evaluate the extrusion process and the physical appearance of filaments made of a hydrophilic polymer and a non-molten model drug. Metformin was used as model drug and Affinisol™ 15LV as the main carrier. Drug-loaded filaments were obtained by using a single-screw extruder and, subsequently, their printability was tested. Blends containing up to a 60% and 50% drug load with 5% and 7.5% of auxiliary excipients, respectively, were successfully extruded. Between the obtained filaments, those containing up to 50% of the drug were suitable for use in FDM 3D printing. The studied parameters, including residence time, flow speed, brittleness, and fractal dimension, reflect a critical point in the extrusion process at between 30-40% drug load. This finding could be essential for understanding the behaviour of filaments containing a non-molten component.